EFFECT OF WASTE FOUNDRY SAND ON FLEXURAL STRENGTH AND WATER ABSORPTION OF CONCRETE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Presently, the construction industry is constantly expanding on a huge scale and incorporating new techniques for quick and comfortable field labor. Concrete, being a construction material, plays a significant part in this industry. The cost of using natural resources as concrete materials is significant, and it is on the edge of becoming exorbitant. These issues urge us to either restore natural resources or discover another way to solve the situation. Waste foundry sand, which is produced as a byproduct of the metal casting industry, currently creates a variety of environmental issues. The use of this waste as a building material might help to reduce environmental stress.